The Role of ADHD in Predicting the Development of Violent Behavior Among Juvenile Offenders: Participation Versus Frequency - Wojciechowski, Thomas W. (Journal of interpersonal violence, 2021)
Past research has identified attention-deficit/hyperactivity disorder (ADHD) as a risk factor for engagement in violent offending. Despite the link between the disorder and violent offending, this risk factor has yet to be examined as a predictor of heterogeneity in the development of violent offending among juvenile offenders. It is likely that the impulsivity, genetic link, and generally chronic disorder course which are characteristics of the disorder play roles in predicting violent offending, which is consistent with both self-control theory and general developmental theory related to early life deficits and life-course persistent offending. Past research has also elucidated a developmental trajectory model of violent offending, which is utilized by the present research. The present research examines ADHD as a risk factor predicting trajectory group assignment. The Pathways to Desistance data followed 1,354 juvenile offenders for 84 months following conviction for a serious offense. Using multinomial logistic regression, this study extends past research on the development of violent offending among juvenile offenders by examining ADHD as a risk factor predicting assignment to violent offending trajectory groups. Results indicate that meeting criteria for ADHD at baseline predicted membership to all trajectory groups relative to the Abstaining group when all covariates were included. This increase in risk is highest for the trajectory group characterized by the highest frequency of violent offending. This indicates the relevance of identifying and treating ADHD among juvenile offenders to best mitigate risk of violent recidivism throughout adolescence and early adulthood.